TINJAUAN KITAB SYARAH SUNAN ABI DAWUD â€œBazdl Al-Majhud Fi Halli Aby Dawudâ€ - Rasyad, Rasyad (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2018)
This paper attempts to find one of Sunan Abi Dawud's scholarly books: